Superelectrophilic activation of 5-hydroxymethylfurfural and 2,5-diformylfuran: organic synthesis based on biomass-derived products - Ryabukhin, Dmitry S.; Zakusilo, Dmitry N.; Kompanets, Mikhail O.; A.Tarakanov, Anton; Boyarskaya, Irina A.; Artamonova, Tatiana O.; Khohodorkovskiy, Mikhail A.; Opeida, Iosyp O.; Vasilyev, Aleksander V. (Beilstein Journal of Organic Chemistry, 2016)
The reaction of 5-hydroxymethylfurfural (5-HMF) with arenes in superacidic trifluoromethanesulfonic acid (triflic acid, TfOH) as the solvent at room temperature for 1–24 h gives rise to 5-arylmethylfurfurals (yields of 17–91%) and 2-arylmethyl-5-(diarylmethyl)furans (yields of 10–37%). The formation of these two types of reaction products depends on the nucleophilicity of the arene. The same reactions under the action of acidic zeolites H-USY in high pressure tubes at 130 °C for 1 h result in the formation of only 5-arylmethylfurfurals (yields of 45–79%). 2,5-Diformylfuran (2,5-DFF) in the reaction with arenes under the action of AlBr3 at room temperature for 1 h leads to 5-(diarylmethyl)furfurals (yields of 51–90%). The reactive protonated species of 5-HMF and 2,5-DFF were characterized by NMR spectroscopy in TfOH and studied by DFT calculations. These reactions show possibilities of organic synthesis based on biomass-derived 5-HMF and 2,5-DFF.
Keywords: 2,5-diformylfuran; Friedel–Crafts reaction; 5-hydroxymethylfurfural; superacids; zeolites

(untitled) - Barta, K.; Ford, P. C. (Acc. Chem. Res., 2014)

(untitled) - Colmenares, J. C.; Luque, R. (Chem. Soc. Rev., 2014)

(untitled) - Straathof, A. J. J. (Chem. Rev., 2014)

(untitled) - Besson, M.; Gallezot, P.; Pinel, C. (Chem. Rev., 2014)

(untitled) - Moiseev, I. I. (Russ. Chem. Rev., 2013)

(untitled) - Alonso, D. M.; Wettstein, S. G.; Dumesic, J. A. (Chem. Soc. Rev., 2012)

(untitled) - Gallezot, P. (Chem. Soc. Rev., 2012)

(untitled) - Ponomarev, A. V.; Ershov, B. G. (Russ. Chem. Rev., 2012)

(untitled) - Sun, N.; Rodriguez, H.; Rahman, M.; Rogers, R. D. (Chem. Commun., 2011)

(untitled) - Varfolomeev, S. D.; Efremenko, E. N.; Krylova, L. P. (Russ. Chem. Rev., 2010)

(untitled) - Marshall, A.-L.; Alaimo, P. (Chem. – Eur. J., 2010)

(untitled) - Stöcker, M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Chheda, J. N.; Huber, G. W.; Dumesic, J. A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Huber, G. W.; Corma, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Corma, A.; Iborra, S.; Velty, A. (Chem. Rev., 2007)

(untitled) - Huber, G. W.; Iborra, S.; Corma, A. (Chem. Rev., 2006)

(untitled) - Bozell, J. J.; Petersen, G. R. (Green Chem., 2010)

(untitled) - Kamm, B. (Angew. Chem., Int. Ed., 2007)

(untitled) - van Putten, R.-J.; van der Waal, J. C.; de Jong, E.; Rasrendra, C. B.; Heeres, H. J.; de Vries, J. G. (Chem. Rev., 2013)

(untitled) - Kashin, A. S.; Galkin, K. I.; Khokhlova, E. A.; Ananikov, V. P. (Angew. Chem., Int. Ed., 2016)

(untitled) - Galkin, K. I.; Krivodaeva, E. A.; Romashov, L. V.; Zalesskiy, S. S.; Kachala, V. V.; Burykina, J. V.; Ananikov, V. P. (Angew. Chem., Int. Ed., 2016)

(untitled) - Li, W.; Xu, Z.; Zhang, T.; Li, G.; Jameel, H.; Chang, H.; Ma, L. (BioResources, 2016)

(untitled) - Choudhary, V.; Mushrif, S. H.; Ho, C.; Anderko, A.; Nikolakis, V.; Marinkovic, N. S.; Frenkel, A. I.; Sandler, S. I.; Vlachos, D. G. (J. Am. Chem. Soc., 2013)

(untitled) - Hu, L.; Zhao, C.; Tang, X.; Wu, Z.; Xu, J.; Lin, L.; Liu, S. (Bioresour. Technol., 2013)

(untitled) - Yang, J.; De OliveiraVigier, K.; Gu, Y.; Jérôme, F. (ChemSusChem, 2015)

(untitled) - Iesce, M. R.; Sferruzza, R.; Cermola, F.; DellaGreca, M. (Helv. Chim. Acta, 2016)

(untitled) - Palframan, M. J.; Pattenden, G. (Chem. Commun., 2014)

(untitled) - Dijkman, W. P.; Groothuis, D. E.; Fraaije, M. W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ghezali, W.; De Oliveira Vigier, K.; Kessas, R.; Jérôme, F. (Green Chem., 2015)

(untitled) - Liu, F.; Audemar, M.; De Oliveira Vigier, K.; Clacens, J.-M.; De Campo, F.; Jérôme, F. (ChemSusChem, 2014)

(untitled) - Kompanets, M. O.; Kushch, O. V.; Litvinov, Yu. E.; Pliekhov, O. L.; Novikova, K. V.; Novokhatko, A. O.; Shendrick, A. N.; Vasilyev, A. V.; Opeida, I. O. (Catal. Commun., 2014)

Superelectrophiles and Their Chemistry - Olah, G. A.; Klumpp, D. A. (Wiley, 2008)

Superacid Chemistry - Olah, G. A.; Prakash, G. K. S.; Molnar, A.; Sommer, J. (Wiley, 2009)

(untitled) - Prakash, G. K. S.; Paknia, F.; Chacko, S.; Mathew, T.; Olah, G. A. (Heterocycles, 2008)

(untitled) - Klumpp, D. A.; Jones, A.; Lau, S.; de Leon, S.; Garza, M. (Synthesis, 2000)

(untitled) - Klumpp, D. A.; Kindelin, P. J.; Li, A. (Tetrahedron Lett., 2005)

(untitled) - Sheets, M. R.; Li, A.; Bower, E. A.; Weigel, A. R.; Abbot, M. P.; Gallo, R. M.; Mitton, A. M.; Klumpp, D. A. (J. Org. Chem., 2009)

(untitled) - Prakash, G. K. S.; Panja, C.; Shakhmin, A.; Shah, E.; Mathew, T.; Olah, G. A. (J. Org. Chem., 2009)

(untitled) - Cabares, J.; Mavoungou-Gomes, L. (Bull. Soc. Chim. Fr., 1986)

(untitled) - Skrzyńska, A.; Przydacz, A.; Albrecht, Ł. (Org. Lett., 2015)

(untitled) - Onorato, A.; Pavlik, C.; Invernale, M. A.; Berghorn, I. D.; Sotzing, G. A.; Morton, M. D.; Smith, M. B. (Carbohydr. Res., 2011)

(untitled) - Ager, D. J. (Tetrahedron Lett., 1983)

(untitled) - Watanabe, N.; Matsugi, A.; Nakano, K.; Ichikawa, Y.; Kotsuki, H. (Synlett, 2014)

(untitled) - Gomes, R. F. A.; Coelho, J. A. S.; Frade, R. F. M.; Trindade, A. F.; Afonso, C. A. M. (J. Org. Chem., 2015)

(untitled) - Pérez, M.; Mahdi, T.; Hounjet, L. J.; Stephan, D. W. (Chem. Commun., 2015)

(untitled) - Miao, M.; Luo, Y.; Li, H.; Xu, X.; Chen, Z.; Xu, J.; Ren, H. (J. Org. Chem., 2016)

(untitled) - Villain-Guillot, P.; Gualtieri, M.; Bastide, L.; Roquet, F.; Martinez, J.; Amblard, M.; Pugniere, M.; Leonetti, J.-P. (J. Med. Chem., 2007)

(untitled) - Parr, R. G.; van Szentpály, L.; Liu, S. (J. Am. Chem. Soc., 1999)

(untitled) - Chattaraj, P. K.; Giri, S.; Duley, S. (Chem. Rev., 2011)

(untitled) - Alkhafaji, H. M. H.; Ryabukhin, D. S.; Muzalevskiy, V. M.; Vasilyev, A. V.; Fukin, G. K.; Shastin, A. V.; Nenajdenko, V. G. (Eur. J. Org. Chem., 2013)

(untitled) - Alkhafaji, H. M. H.; Ryabukhin, D. S.; Muzalevskiy, V. M.; Osetrova, L. V.; Vasilyev, A. V.; Nenajdenko, V. G. (Russ. J. Org. Chem., 2013)

(untitled) - Koltunov, K. Y.; Shakirov, M. M.; Repinskaya, I. B.; Koptug, V. A. (Zh. Org. Khim., 1991)

(untitled) - Koltunov, K. Y.; Repinskaya, I. B. (Zh. Org. Khim., 1993)

(untitled) - Walspurger, S.; Vasilyev, A. V.; Sommer, J.; Pale, P. (Tetrahedron, 2005)

(untitled) - Rendy, R.; Zhang, Y.; McElrea, A.; Gomeez, A.; Klumpp, D. A. (J. Org. Chem., 2004)

(untitled) - Mühlthau, F.; Stadler, D.; Goeppert, A.; Olah, G. A.; Prakash, G. K. S.; Bach, T. (J. Am. Chem. Soc., 2006)

(untitled) - Olah, G. A.; Spear, R. J.; Forsyth, D. A. (J. Am. Chem. Soc., 1977)

(untitled) - Mascal, M.; Nikitin, E. B. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kumari, N.; Olesen, J. K.; Pedersen, C. M.; Bols, M. (Eur. J. Org. Chem., 2011)

(untitled) - Ennaert, T.; Van Aelst, J.; Dijkmans, J.; De Clercq, R.; Schutyser, W.; Dusselier, M.; Verboekend, D.; Sels, B. F. (Chem. Soc. Rev., 2016)

(untitled) - Sineva, L. V.; Asalieva, E. Yu.; Mordkovich, V. Z. (Russ. Chem. Rev., 2015)

(untitled) - Shi, J.; Wang, Y.; Yang, W.; Tang, Y.; Xie, Z. (Chem. Soc. Rev., 2015)

(untitled) - Dapsens, P. Y.; Mondelli, C.; Pérez-Ramírez, J. (Chem. Soc. Rev., 2015)

(untitled) - Van Speybroeck, V.; Hemelsoet, K.; Joos, L.; Waroquier, M.; Bell, R. G.; Catlow, C. R. A. (Chem. Soc. Rev., 2015)

(untitled) - Primo, A.; Garcia, H. (Chem. Soc. Rev., 2014)

(untitled) - Li, Y.; Yu, J. (Chem. Rev., 2014)